The Effort Handling by the Police to follow Criminal crash Running in the City of Medan - Dahris Siregar; Elyani; Karolina Sitepu; Jamelia; Desman Hulu; Indra Dwi Wahyudi Situmorang; Vhani Wulandari; Rencana Laoli; Hopnes King Hulu (PT Inovasi Pratama Internasional, 2022)
The increasing number of motorized vehicles every year and the negligence of the community which often results in traffic accidents. A traffic accident where the perpetrator is not responsible, by leaving the victim alone without providing help is called a hit and run. The crime of hit and run is a problem that needs to be addressed because it is an immoral act and harms others. Hit-and-run crimes that cause harm to others are increasingly common. Seeing the many factors that cause the occurrence of a hit-and-run crime. Both in terms of community factors, road factors, vehicle factors. Thus the purpose of the problem is to find out the factors causing the occurrence of a hit-and-run crime, Handling Efforts by the Police Against Hit-and-Run Crimes in Medan City. The research methods used are library research and field research at the Medan Police Traffic Unit and using Qualitative Data Analysis. The factors that influence the increase in traffic accidents on the highway are due to the lack of public awareness and compliance to obey and obey every traffic regulation. People always put the blame on law enforcement officers (police) without realizing and filtering their own mistakes first, indeed to create military and order in traffic there must be a good cooperative relationship between law enforcement officers and the community itself, because without the intertwining of the rights and obligations of law enforcement officers and the community, it is impossible to create peace, order and comfort in traffic. This is not just a time when it often happens in the community, but it has been a long time since traffic accidents have developed in the State of Indonesia.